Logic furniture: transformable & convertible lounge chair / Nur Azah Farhana Mohamed Fadzil, Mohd Shaleh M. Mujir and Ruwaidy Mat Rasul - Mohamed Fadzil, Nur Azah Farhana; M. Mujir, Mohd Shaleh; Mat Rasul, Ruwaidy (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
An attractive design of sofa bed inspired by Islamic calligraphy and influence from ottoman. To design a sofa bed is very stylish design looks, nice and cool using the comfortable and durable materials. The main purpose of production is to produce multi - function furniture, whereas sofa can be transformed to bed. It can reduce the problem of the use of lots of space, suitable for small living space and it is easy to use. Basic form and design, transformable & convertible, for purpose & people, and an exploration of cheap and recycle / recyclable material with a bit of mechanism. That is all a clues to be explored in order to produce a "Logic Furniture" in a basic and better way.